2019
DOI: 10.1111/dme.14076
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness analysis of empagliflozin treatment in people with Type 2 diabetes and established cardiovascular disease in the EMPAREG OUTCOME trial

Abstract: AimIn the EMPA‐REG OUTCOME trial, empagliflozin therapy reduced cardiovascular death by 38% compared with placebo when added to standard of care. Using the trial results, we created a discrete‐event simulation model to assess lifetime health economic outcomes in people with Type 2 diabetes and established cardiovascular disease.MethodsTime‐dependent survival regression analysis was performed on data from EMPA‐REG OUTCOME for 10 cardiovascular and renal events (e.g. stroke, heart failure hospitalization, macroa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 18 publications
(14 reference statements)
1
60
0
1
Order By: Relevance
“…Using a participant-level simulation model and United Kingdom health care costs, empagliflozin in addition to standard of care is projected to be cost-effective. 101 The model predicted that although patients would incur increased out-ofpocket cost, empagliflozin in addition to standard of care would result in longer survival by 2.1 life-years. Market exclusivity practice is another major barrier because brand name monopolies may delay widespread access to SGLT2 inhibitors.…”
Section: Benefits and Risks In Different Populationsmentioning
confidence: 99%
“…Using a participant-level simulation model and United Kingdom health care costs, empagliflozin in addition to standard of care is projected to be cost-effective. 101 The model predicted that although patients would incur increased out-ofpocket cost, empagliflozin in addition to standard of care would result in longer survival by 2.1 life-years. Market exclusivity practice is another major barrier because brand name monopolies may delay widespread access to SGLT2 inhibitors.…”
Section: Benefits and Risks In Different Populationsmentioning
confidence: 99%
“…Even with greater awareness of the benefits of SGLT2 inhibitors, their high cost poses a barrier to use. Using a participant-level simulation model and U.K. health care costs, empagliflozin in addition to standard of care is projected to be cost-effective (101). The model predicted that although patients would incur increased out-of-pocket cost, empagliflozin in addition to standard of care would result in Table 5-Proposed research to increase uptake of SGLT2 inhibitors…”
Section: Optimizing Uptake Of Sglt2 Inhibitorsmentioning
confidence: 99%
“…Several studies and conference abstracts reported the cost-effectiveness/utility of empagliflozin, across the perspective of payers in several countries, as monotherapy, dual or triple therapy, or in comparison to the standard of care in individuals with T2DM. [17][18][19][20][33][34][35][36][37][38] A majority of these studies analyzed data from EMPA-REG OUTCOME trial. The results consistently demonstrated that treatment with empagliflozin was found to be cost-effective compared to the BASC treatment in individuals with T2DM and cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…A Microsoft Excel-based patient-level simulation model has been used to assess the pharmacoeconomic profiles of empagliflozin in several other countries. [18][19][20] In this study, the model was adapted to the Chinese setting and applied to determine the cost-utility of empagliflozin versus placebo on top of BASC over a lifetime horizon, from the perspective of Chinese healthcare payer. A total of 5000 patients that randomly sampled from the EMPA-REG OUTCOME trial were simulated for base-case analysis.…”
Section: Model Structurementioning
confidence: 99%
See 1 more Smart Citation